Kikuchi Fujimoto disease: sinister presentation, good prognosis. Issue 1 (2nd January 2021) - Jiwani, Rahim A.; Jourdan, Daniel N.; Pona, Adrian; Donthi, Deepak; Stalls, J. Stephen; Rehana, Rita W.
ABSTRACT: Kikuchi-Fujimoto disease (KFD) is a rare, benign, self-limiting necrotizing lymphadenitis of unknown etiology. The disease can affect people of all ages and of any sex and ethnicity. Tissue biopsy is needed for accurate diagnosis. The condition commonly masquerades as more sinister conditions such as malignancy and rheumatologic disorders, but has a much better prognosis. Treatment is generally supportive but patients may require corticosteroids with eventual spontaneous resolution. We discuss a case of KFD in a 34-year-old male and highlight the need for prompt and accurate diagnosis.